The Concept Of Integrating MI Science With Islamic Science - Zainul Anwar; Yuni Masrifatin (Mentari : Journal of Islamic Primary School, 2025)
In an effort to address the dichotomy between general sciences and religious sciences in Islamic education in Indonesia, this article explores the concept of integrating Islamic knowledge with general sciences. The article aims to highlight the importance of integration between religious and general knowledge in Islamic education and to describe its implementation in the context of madrasah ibtidaiyah (Islamic elementary schools). This study employs a literature review by collecting information from various relevant scholarly sources, presenting it descriptively, and applying a qualitative analytical approach to connect the information and draw conclusions. The integration of Islamic knowledge with general sciences in madrasah ibtidaiyah aims to develop students with religious character, moral integrity, knowledge, and skills relevant to the demands of the times. This effort involves various approaches in character education and emphasizes the need for harmony between religious and general knowledge. The integration of Islamic and general sciences in Islamic education at madrasah ibtidaiyah has significant implications for creating a generation that possesses balanced knowledge, character, and relevance to contemporary challenges.